074 The temporary tattoo project. (December 2018) - Moore, C; Drummond, D
Abstract : Background and objectives: Just 25% of Great Ormond Street Hospital (GOSH) inpatients are over the age of 13 and subsequently they can often feel isolated. These young people like all long term patients are also missing out on key social and cultural opportunities. GOSH Arts (the hospital's arts programme) invited artist Davina Drummond to work with young people at GOSH to explore what it means to be a young person in hospital and how they cope with the challenges it creates. Methods: Davina worked with over 40 young people in inpatient wards over 10 full days. During the supported sessions the young people talked about what kept them strong whilst in hospital and how they coped with their illness, they then experimented with typography and illustration to create graphic designs which conveyed their coping mechanisms. These designs were translated into temporary tattoo designs by Davina and illustrator Ella Bell in consultation with the young people. Results: The designs were printed to create a limited edition set of temporary tattoos. These were given to project participates and other young people at GOSH, letting them know they are not alone in their hospital experience and that like the temporary tattoos not all experiences or situations, especially when in hospital, are permanent. Conclusion: The discussions and temporary tattoos that have come out of the project allowed young people to reflect on the challenges they face as young people in hospital, process their hospital experience and share the techniques they use to cope with their illness with others.